Determinants of sustainable development of industrial enterprises in Poland in the period from 2010 to 2019 – a statistical evaluation - Misztal, Anna; Kowalska, Magdalena (Determinanty zrównoważonego rozwoju przedsiębiorstw przemysłowych w Polsce w latach 2010-2019 – ocena statystyczna, 2020)
The main aim of this paper is to assess the impact of internal and external determinants for the sustainable development of industrial enterprises in Poland in the period from 2010 to 2019. The sustainable development of enterprises means the development in economic, social and ecological spheres. Its level depends on a number of external factors, which, for the needs of the study, have been identified with the quantitative socio-economic development of the country, and internal factors, which have been limited to assessing the financial situation. The first part of this paper presents the basic theoretical issues related to sustainable development and its determinants. The second, main part presents the results of the study, which show that both internal and external factors affect the sustainable development of enterprises. In the vast majority of cases, macroeconomic factors have a greater impact
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 1, s. 160-173
Keywords: sustainable development of enterprises; determinants of the development; zrównoważony rozwój przedsiębiorstwa; determinanty rozwoju